IoT Based Water Tank Level and Turbidity Detection and Monitoring System - Mohamed Jumaiedy, Ilya Suhaida; Suratkon, Azeanita (Recent Trends in Civil Engineering and Built Environment, 2025)
Addressing the need for efficient water monitoring in terms of volume and turbidity in residential settings, an IoT-based solution is proposed. Utilizing Blynk apps for smartphone integration, the system employs ultrasonic and turbidity sensors to accurately measure water levels and quality in residential tanks. The collected data is transmitted to a microcontroller, processed, and displayed on a smartphone for user convenience. The project focuses on comprehensive design, prototype development, and usability analysis, aiming to promote water conservation, optimize tank management and ensure a continuous supply of clean water. The user-friendly interface enables real-time monitoring and customizable alerts, empowering homeowners to safeguard their water supply and mitigate issues related to shortages and contamination.